The Effect of Self-Regulation on Academic Procrastination on Students with Learning Disabilities at School - Sulistyowatia, Yunis Dyah Ayu Ratih (Academia Edu Cendekia Indonesia (AEDUCIA), 2023)
Academic procrastination is a problem that occurs in students in the school environment. Academic procrastination is closely related to failure in self-regulation (self-regulation). Self-regulation refers to self-generated thoughts, feelings, and behaviors that are oriented towards achieving personal goals (Park & Sperling, 2012; Zimmerman, 2000). Individuals who havelow self-regulationtend to do acts of procrastination, because of the ability to doself-regulation or self-regulation is an important factor influencing the emergence of procrastination behavior in students (Steel, 2007) Students with Learning Disabilities (LD) were found to experience lower levels of regulation than their Non Learning Disabilities (NLD) counterparts due to incorrect theories about self, task, and effort required (Butler, 1996; Pintrich, Anderman, & Klobucar, 1994) and because of difficulty in choosing. , implement, and monitor appropriate learning strategies.